EUS guided fine needle aspiration cytology of liver nodules suspicious for malignancy: yields, complications and impact on management. - Varayu Prachayakul (2018)
To examine the sensitivity of endoscopic ultrasonography (EUS) guided Fine needle Aspiration of liver nodules in patients suspected of having primary and metastatic malignancy, as well as the sonographic characteristics of liver nodules, complications and impact on long-term treatment. The medical records and endoscopic reports of 14 patients, performed by single endoscopist, who underwent EUS guided FNA of liver nodules from January 2009 to December 2010 and who were enrolled in the present study. 12 male and 2 female patients were enrolled, aged between 53-82 median 63 years. 21% of the cases were hepatocellular carcinoma. The sensitivity of diagnosis of malignant liver lesions according to cytology was 78.5%. When the clinical course and pathology which indicated atypical cells were combined, the sensitivity was 100% for malignancy. There were no complications after the procedure. The impact on the treatment plan was 64%. The sensitivity for EUS guided FNA for liver nodules which were suspicious for liver malignancy was high. No complications were observed and the pathology results had 64% impact on the treatment plan.